Implementasi Self-Service untuk Membantu Calon Pasien Rumah Sakit - Vannia Ferdina; Genesius Hartoko Soekoco; Junitania Ryanto; Hans Rafael; Eka Cahya Rahmadhani (ULTIMA InfoSys, 2014)
Nowadays the need for patients to receive prompt and proper care of the hospital plays an important role for the development of the hospital itself. This encourages to the development of various applications and integrated system for enhancing the effectiveness of hospital services, one of which is a self-service method to open floor directory and to enroll oneself with a doctor at the hospital. Therefore, in this paper the authors make the design of an application to support the self-service method. The design of the application is made by using the Unified Modeling Language that is represented by use case and class diagram. Index Terms - UML, use case diagram, class diagram